2013
DOI: 10.1099/mic.0.063396-0
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory mechanism of 2,4,6-trichlorophenol catabolic operon expression by HadR in Ralstonia pickettii DTP0602

Abstract: Ralstonia pickettii DTP0602 utilizes 2,4,6-trichlorophenol (2,4,6-TCP) as its sole source of carbon. The expression of catabolic pathway genes (hadA, hadB and hadC) for 2,4,6-TCP has been reported to be regulated by the LysR-type transcriptional regulator (LTTR) HadR. Generally, coinducers are recognized as being important for the function of LTTRs, and alteration of the LTTR-protection sequence and the degree of DNA bending are characteristic of LTTRs with or without a recognized coinducer. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The HadR protein was proved to bind to the promoter of the hadX gene, and the formation of the HadR-deoxyribonucleic acid (DNA) complex was found to be induced by 16 different phenol derivatives. However, only seven of these substituted phenols induced transcription of the hadXABC operon in vivo (Torii, Machida, Hara, Hatta, & Takizawa, 2013). The expression of the second had gene cluster containing the gene encoding MR ( Figure 10) seems to be negatively controlled by another LysR-type regulator HadS (Hatta et al, 2012).…”
Section: Common Transcriptional Regulation Of a Peripheral And A Centmentioning
confidence: 99%
“…The HadR protein was proved to bind to the promoter of the hadX gene, and the formation of the HadR-deoxyribonucleic acid (DNA) complex was found to be induced by 16 different phenol derivatives. However, only seven of these substituted phenols induced transcription of the hadXABC operon in vivo (Torii, Machida, Hara, Hatta, & Takizawa, 2013). The expression of the second had gene cluster containing the gene encoding MR ( Figure 10) seems to be negatively controlled by another LysR-type regulator HadS (Hatta et al, 2012).…”
Section: Common Transcriptional Regulation Of a Peripheral And A Centmentioning
confidence: 99%
“…Torii et al . [111] investigated how HadR regulates 2,4,6-TCP catabolic pathway gene expression in Ralstonia pickettii DTP0602. They found that purified HadR binds to the hadX promoter and HadR–DNA complex formation is induced in the presence of 16 types of substituted phenols, including CPs, nitrophenols and tribromophenols.…”
Section: Introductionmentioning
confidence: 99%
“…These LTTRs cause the inducer-dependent shortening of the protected region from positions −80 to −20 to positions −80 to −30 and then a relaxation of the DNA bending. This was thought to be important in the release of the recognition site of RNA polymerase and the conformational change of regulator-DNA complex suitable for transcriptional activation (Toledano et al, 1994 ; Wang and Winans, 1995a , b ; van Keulen et al, 2003 ; Porrua et al, 2007 ; Torii et al, 2013 ; Kubota et al, 2014 ). Nevertheless, in this study, the behavior of PnpM toward the pnpCDEFG promoter is somewhat different from the sliding dimer model for most LTTRs.…”
Section: Discussionmentioning
confidence: 99%